A conceptual framework for Web-based intelligent learning environments using SCORM-2004 - Sabbir Ahmed Kazi (IEEE International Conference on Advanced Learning Technologies, 2004)
Having a functional Web-based learning environment is a norm for a large number of educational institutions today. But publishing plain e-learning materials in this environment does not contribute significantly to student's learning unless a sound pedagogical framework is adopted behind this process. Substantial researches have been done in the area of adaptive and intelligent tutoring systems to develop Web-based intelligent learning environments (WILE) where the student's current knowledge about the subject matter is stored in a student model database and therefore the materials are presented according to the student's learning need. In most cases, contents are an intrinsic part of these kind of learning environments, and difficult to port to another environment in the case of reuse. This paper introduces a framework to develop dynamic content for a SCORM-conformant Web-based intelligent learning environment that can be ported to another similar kind of learning environment.